Aetiology and outcome of patients burned from 2003 to 2008 at the Tygerberg Hospital burns unit, Western Cape, SA - Maritz, David (Division of Emergency Medicine, 2014)
Rural to urban migration to major cities in South Africa continues to lead to the proliferation of informal settlements. There is little recent published data on the epidemiology of adult burns in the Western Cape, South Africa. The prediction of outcome in severe burns is important to aid in clinical decision making, improve scarce resource allocation and allow comparisons between different burn units. Age, burn size and the presence of inhalational injury have been determined to be the most important factors in predicting mortality. There is little published data on the outcome of severe burns in the Southern African region. A retrospective review of patients on the Burn Unit database was undertaken, looking at patients admitted to the Burn Unit between January 2003 and December 2008. This study discusses the characteristics and outcome of patients who were treated at the Tygerberg Burn unit. A total of 1908 patients were admitted to the burn unit during the 6 year period under review. Most fatal injuries occurred in the 20 to 40 year age group. Injuries due to shack fires and fuel stoves comprised 21% (399) of all admissions. Mortality due to these injuries comprised 28% (137) of total mortality. Gas stoves accounted for 24% with kerosene stoves accounting for 71% of injuries. The burn death rate in this study (25%) was found to have increased dramatically from the last audit done from 1986 to 1995 in which a burn death rate of 7.5% was observed. Reasons for this are explored. A stepwise logistic regression analysis was done on the derivation cohort where age, gender, TBSA% and presence of inhalational injury were identified as significant for predicting death. A mortality prediction model is presented which was internally validated on the validation cohort. An easy to use EXCEL calculator was created to estimate the probability of death. Shack fires and injuries due to fuel stoves are a common reason for admission to the burn unit and mostly involve young male individuals. Other research from the Southern African region does not mention shack fires as a separate entity making it difficult to obtain an accurate idea of the scale of the problem. Their injuries are severe with a high mortality. The use of kerosene stoves are a major contributing factor. Recommendations include enforceable legislation to promote safer stove design, research into safer bio fuels and materials for building shacks as well promoting fire safety among schoolchildren in the community. Further research is needed to determine the impact of HIV/AIDS on the outcome of acute burn injuries within the Southern African region. Further interventions are needed to tackle this serious public health issue. A mortality prediction model is proposed for use in the burn unit, but needs external validation before being adopted into clinical practice. Further research is needed to improve data capturing in the burn unit.